2011
DOI: 10.1590/s1415-790x2011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Bens de consumo e insegurança alimentar: diferenças de gênero, cor de pele autorreferida e condição socioeconômica

Abstract: OBJETIVO: Com base nos dados da Pesquisa Nacional por Amostra de Domicílios (PNAD, 2004), foram comparadas as diferenças na prevalência de insegurança moderada/grave em relação à segurança alimentar, e insegurança leve quanto à posse de bens de consumo e outras condições socioeconômicas e demográficas. MÉTODOS: Foram estudados os domicílios particulares permanentes, com rendimento domiciliar per capita de até um salário mínimo, utilizando-se a Escala Brasileira de Insegurança Alimentar respondida por morador d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 13 publications
4
17
1
28
Order By: Relevance
“…Although the level of education of the household head was not included in the final model of multiple multinomial regression, it was inversely associated with FI, which is consistent with the findings of other studies 9,10 . Level of education is directly related to higher earnings 18,19 , which in turn, can determine the consumption pattern of the population.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although the level of education of the household head was not included in the final model of multiple multinomial regression, it was inversely associated with FI, which is consistent with the findings of other studies 9,10 . Level of education is directly related to higher earnings 18,19 , which in turn, can determine the consumption pattern of the population.…”
Section: Discussionsupporting
confidence: 87%
“…Like the PNAD 2004 data, the data from the present study also showed that the higher the score of the presence of household goods and services, the lower the risk of FI 9 ; the possession of goods or services may indicate not only their current financial situation but also a history of better financial conditions or the priority that those families give to the management of their earnings.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Em relação aos fatores associados, o estudo confirmou as evidências de publicações internacionais 27 e nacionais 18,20,29,30 , que destacam o papel fundamental da renda na determinação da insegurança alimentar e de iniquidades em sua ocorrência. Portanto, as estratégias de incremento de renda em populações vulneráveis por meio do Bolsa Família e de outros benefícios so-ciais são essenciais e precisam ser mais efetivas e equânimes.…”
Section: Discussionunclassified